Functional and self-care capacity of people with multiple sclerosis - Ana Railka de Souza Oliveira-Kumakura; Larissa Maria Bezutti; Juliany Lino Gomes Silva; Renata Cristina Gasparino
Objective: describe the self-care and functionality levels of patients with multiple sclerosis and determine whether sociodemographic, clinical and functional variables interfere with self-care and/or functionality. Method: correlational, cross-sectional study with a quantitative approach performed with individuals in outpatient follow-up. We collected sociodemographic and clinical data and applied the Appraisal of Self-care Agency Scale, the Barthel index, the Lawtton and Brody Scale, and the instrument to investigate the performance in Advanced Activities of Daily Living. We performed descriptive and inferential analysis. Results: most patients were classified as "having self-care" (82.14%); with moderate dependence (51.19%) for the basic activities of daily living, partial dependence for the instrumental activities of daily living (55.95%), and more active for the advanced activities of daily living (85.71%). Patients with longer disease duration had a higher number of disabilities and, in those with better socioeconomic and educational profile, the functionality was better. Conclusion: disease duration was strongly correlated with a higher number of disabilities and better socioeconomic and educational profiles showed to be protective factors for functionality. Care planning should consider the needs observed by the multidisciplinary team, stimulating the development of self-care, functionality and sociability.